Politics and the Life Sciences: The Rise of a New Framework. (11th November 2020) - Murray, Gregg R.; Beall, Anne; Fletcher, Amy; Grillo, Michael C.; Senior, Carl; Mansell, Jordan
Abstract : Some would argue there is a global movement afoot to study "biopolitics." More and more scholarly reports that help shape our understanding of the political domain from this perspective are filling the pages of research journals. This is an important era of increasing scholarly interest in the intersection of the political and biological worlds and the rapidly evolving analytical innovations available to explore this still under-explored domain. With the arrival of these new opportunities comes a new editorial team at Politics and the Life Sciences ( PLS ). It is a team that extends its appreciation to the Council of the Association for Politics and the Life Sciences for the trust they put in it to steer the journal forward at this interesting and critical time. As well, it is a team that expresses its heartfelt gratitude to its immediate predecessors, Tony Wohlers, Maggie Kosal, and their editorial colleagues, for their determined leadership of the journal over the last three years and the easy transition they facilitated for the new team. They clearly laid a firm foundation for the next stage of the development of the journal.